437 Adolescents with Life-Limiting Illnesses - are We Taking a Sexual History?. (October 2012) - Finlay, F; Onugha, NN
Abstract : Introduction: Talking to adolescents about sex can be difficult for health professionals - they may not know how to begin the conversation, may feel embarrassed or ill-prepared, may feel they do not have enough time or it is not relevant to their consultation. Many adolescents are having sex and adolescents with life-limiting illnesses are no exception. Giving them the opportunity to talk about sex during consultations is therefore important. Aim: A literature review revealed no previous studies on this topic. Our aim was to review medical consultations of adolescents with life-limiting illnesses and establish whether sex was discussed. Method: A retrospective review of clinical notes of adolescent patients with life-limiting illnesses was carried out with a view to establishing whether a sexual history was taken on any occasion. Results: None of the healthcare professionals took a sexual history from any of the adolescents on any occasion despite multiple clinic attendances. Discussion: Doctors tend to focus on the 'clinical' aspects of sexual health such as prescribing contraception and testing for sexually transmitted diseases, omitting sexual concerns and sexuality. Clinicians may struggle to accept that adolescents with life-limiting illnesses may want to talk about sex and this study has highlighted that it is a topic which is generally ignored. It is the responsibility of clinical departments to train their staff in sexual history taking, an important aspect of healthcare. Conclusion: Health professionals should include sexual health in routine palliative assessments so that every adolescent is given an opportunity to be heard.